The Trinity
XVIII, 264 p.
Keywords: East/West Summit on the Holy Trinity Held in Moscow - A stellar cast from the Society of Christian Philosophers/West and the Russian Orthodox Church/East met to discuss the mystery of God as three in one. Theologians and philosophers, typically rivals, synergized in their pursuit of truth and understanding regarding this central, unifying Christian belief, demonstrating respective strengths in marvellous complementary array. His holiness Alexei II, Patriarch of Moscow and all Russia extended greetings and Metropolitan Filaret of Minsk set the stage. History still has its shining moments. The next best thing to being there are the papers that were presented and polished for this volume.